Value added service entrepreneurship development through Melaka K-Economy incubator complex - Ismail, Ishak; Hassan, Ismail; Mat Jusoh, Normal (2002)
Since 1st. April 2001, Melaka State has embarked on a programme to develop value added service entrepreneurship through Melaka K-Economy Incubator Complex. The idea draws on the principle of interdependency and sustainability through many overlapping network system and system of clusters which have shown to be more robust and developmentally successful. Many authors such as Gouranga Gopal Das 1 has shown some quantitive evidence of the interdependency of Trade, Technology and Human Capital. This paper has brought the idea further in suggesting the implementation procedures which can be followed by developing countries such as Melaka which is striving to be an industrialised state by the year 2010. The implementation procedures feeds on the logic that as the rural areas are the geographical location where there is a sufficient density of human population with lower intensity of activities and a marked density of creativity; these areas should be a subset of the innovation system which can become a catalyst to the K-Economy development of any country. Many practices so far has neglected and ignored the role of the rural areas in the economic development of a nation other than the fact that they provide a pool of cheap labour. Initial surveys done in Melaka has shown some indication that contrary to present practices, rural areas play a significant role in the economic development of a nation because potentially they are capable of providing knowledge workers and creativity factors which are essential for the growth of value-added businesses. The paper also discusses the structure of the internetworking which is employed to maximise the effectiveness of the knowledge factor. This internetworking takes into consideration the division of focus and division of skills in delivering three important elements of the innovation system; viz-a-viz business capability, research capability and development & design capability.